Value-based Health Care and Cost-containment Innovation Amid Rising Global Health Expenditure: A Critical Review of Strategies, Constraints and Evidentiary Foundations - Rhoda Ofosua Holdbrook; Peter Aduvie Josiah; Chiamaka Pamela Agu; John Lazule Akoumah (Journal of Disease and Global Health, 2026)
Health expenditure continues to expand faster than national income in most economies, and the fiscal space available to absorb that expansion has narrowed since the coronavirus disease 2019 pandemic. Value-based health care has become the dominant policy vocabulary for reconciling rising cost with sustained or improved outcomes, and it now coexists with an older repertoire of cost-containment instruments spanning payment reform, price regulation, health technology assessment and the removal of low-value services. This critical narrative review examines how far the empirical record supports the claims made for these strategies, where the evidence is strongest, and where confident assertion has outrun demonstration. Literature was identified through structured searching of PubMed, Europe PMC, OpenAlex, Crossref, OpenAIRE and EconBiz, supplemented by citation chaining and by expenditure statistics from intergovernmental sources, with a final search date of 22 June 2026. The synthesis is organised around six analytical problems rather than around individual studies: the contested definition of value and its measurement infrastructure; the differential performance of payment models; the behaviour of price-side and technology-side instruments; the persistent gap between estimated waste and recoverable savings; the distributional consequences of value-based contracting; and the transferability of high-income reform templates to lower-income financing systems. Evidence of spending restraint is reasonably consistent for episode-based payment in lower-extremity joint replacement, for global budgeting in a single well-studied jurisdiction, and for competitive off-patent markets in pharmaceuticals. It is weak or contested for penalty-based quality incentives, for artificial intelligence as a cost-reducing technology, and for the proposition that documented waste is largely recoverable. Measured value remains partly endogenous to coding behaviour, which complicates causal interpretation of programme evaluations. Priority should shift from generating further descriptive implementation accounts towards designing evaluations capable of distinguishing genuine efficiency gains from measurement artefact, cost shifting and favourable patient selection.